The effects of acute ethanol administration on ethanol withdrawal-induced anxiety-like syndrome in rats: A biochemical study - Kumar, Jaya; Hapidin, Hermizi; Get Bee, Yvonne-Tee; Ismail, Zalina (2016)
Withdrawal from long-term ethanol consumption results in overexcitation of glutamatergic neurotransmission in the amygdala, which induces an anxiety-like syndrome. Most alcoholics that suffer from such symptoms frequently depend on habitual drinking as self-medication to alleviate their symptoms. Metabotropic glutamate receptor subtype 5 (mGlu5) and protein kinase C (PKC) epsilon have been reported to mediate acute and chronic effects of ethanol. This study explores the changes in mGlu5 and PKC epsilon in the amygdala following acute administration of ethanol during ethanol withdrawal (EW) induced anxiety. Male Wistar rats were fed a modified liquid diet containing low-fat cow milk, sucrose, and maltodextrin, with a gradual introduction of 2.4%, 4.8% and 7.2% ethanol for 20 days. Six hours into EW, the rats were intraperitoneally injected with normal saline and ethanol (2.5 g/kg, 20% v/v), and exposed to open-field and elevated plus maze tests. Then, amygdala tissue was dissected from the rat brain for Western blot and gene expression studies. EW-induced anxiety was accompanied by a significant increase in mGlu5, total PKC epsilon, and phosphorylated PKC epsilon protein levels, and also of mRNA of mGlu5 (GRM5) in the amygdala. Acute administration of ethanol significantly attenuated EWinduced anxiety as well as an EW-induced increase in GRM5. The acute challenge of ethanol to EW rats had little effect on the phosphorylated and total protein levels of PKC epsilon in the amygdala. Our results demonstrate that amygdala PKC epsilon may not be directly involved in the development of anxiety following EW.